ANALYSIS OF A SEQUENTIAL JAVA CODE FOR AUTOMATICPARALLELIZATION IN DISTRIBUTED NETWORKS FOR HIGH PERFORMANCE COMPUTING –A RUNTIME APPROACH - Ms. Sonam Shaikh; Prof. Mr.Anil Patil (International Journal of Innovations in Engineering Research and Technology, 2021)
The popularity of the Internet and the availability of powerful computers and high-speed networks as low cost commodity components are changing the way we use computers today. This technology opportunity has led to the possibility of using networks of computers as a single, unified computing resource. Itis possible to use multiple computers as a single unified resource for high performance computing. The Java Development Environment (JDE) includes several features which facilitate the production of stable, robust code for parallel processing. Threads provide an efficient and effective paradigm for utilizing tightly coupled systems and socket communication, remote method invocation (RMI) are for distributing environments. The work focuses on an automatic parallelization of a Java code to improve the performance of a program execution. At run time it parallelizes the code for execution. The research focuses on a new parallel execution technique in which the sequential java code is analyzed and parallelized so that each part of code is executed on different system in a network in accordance with the availability of the computers in a network. It speeds up the execution of a particular application to a great extent.